STUDY OF TRADITIONAL METHODS OF PLANTING FRUIT TREE SEEDLINGS AND DESIGNING A PLANTING MACHINE (Multidisciplinary Journal of Science and Technology, 2025)
This article presents the traditional methods of planting fruit tree seedlings on agricultural fields allocated for establishing fruit orchards, in accordance with agrotechnical standards. Since these traditional methods are highly labor-intensive, costly, and time-consuming, the paper proposes design considerations for developing a fully mechanized seedling planting machine. The envisioned machine would ensure high efficiency, reduced costs, and continuous planting of fruit tree seedlings in a short time, all while adhering to agro-technical requirements.